A RARE CASE OF COMPLETE VAGINAL PROLAPSE IN AN ADVANCED PREGNANT BITCH - JAYAKUMAR, C; SUDHA, G; KANTHARAJ, S; IMAM HUSSAIN, G (The Indian Journal of Animal Reproduction, 2016)
A six-year-old crossbred bitch had complete vaginal prolapse as a complication to increased intra-abdominal pressure from ascites of hepatic origin and full term pregnancy. The recurrence of vaginal prolapse and ascites was not observed following surgery and therapeutic management